Market Channels in Agro-forestry Products - a Case Study of Yamunanagar, Haryana - Negi, M. S.; Ansari, M. Y.; Singh, H. P. (Indian Forester, 2001)
The tree growers of Yamunanagar District used various channels for selling their trees/produce; viz. Traders - Industries, Village level Agents/Contractors - Traders - Industries, Village level Agents/Contractors - Saw mills - Consumers, Traders - Saw mills - Consumers and Traders - Other markets of the State. It was found that 73 per cent of tree growers prefer through village agents, 23 per cent traders and only 4 per cent industries. It was also observed that socioeconomic factors such as literacy level, education and even family size do not have any significant effect on choice of market channels.